The Echo Sounder simulator unit based on microcomputer systems - Mohamad Isa Mansor (University of Hull, 2011)
The aim of the project is to study the possibility of using a microcomputer system to implement an echo sounder simulation. The design flexibility of the microprocessor software enables the development of a simulation program necessary to produce an echo signal suitable for a conventional echo sounder. An optional colour display is provided to give a simultaneous recording of the targets. The colour display is generated on a colour t.v. with a colour display generator capable of providing up to seven colours to represent the varying echo intensity. Also a demonstration of mid-water trawling manoeuvre is provided on the colour display.